The impacts of the early outset of the COVID-19 pandemic on climate change research: Implications for policy-making. Issue 124 (October 2021) - Leal Filho, Walter; Wall, Tony; Alves, Fatima; Nagy, Gustavo J.; Fernández Carril, Luis Ricardo; Li, Chunlan; Mucova, Serafino; Platje Joost, Johannes; Rayman-Bacchus, Lez; Totin, Edmond; Ayal, Desalegn Y.; Lütz, Johannes M.; et al.
Graphical abstract: Highlights: The COVID-19 has impacted climate change researchers, creating additional work. The use of communication technologies has helped to alleviate the problems. A positive impact is that researchers were able to develop new research ideas. The pandemic is likely to alter the course of climate change research. Most of the surveyed respondents report that they can adequately cope with the problems. Abstract: Since January 2020, the COVID-19 pandemic has dominated the media and exercises pressure on governments worldwide. Apart from its effects on economies, education systems and societies, the pandemic has also influenced climate change research. This paper examines the extent to which COVID-19 has influenced climate change research worldwide during the first wave at the beginning of 2020 and how it is perceived to exploit it in the future. This study utilised an international survey involving those dedicated to climate change science and management research from Academia, Government, NGOs, and international agencies in 83 countries. The analysis of responses encompasses four independent variables: Institutions, Regions, Scientific Areas, and the level of economic development represented by the Human Development Index (HDI). Results show that: (1) COVID-19 modified the way the surveyed researchers work, (2) there are indicators that COVID-19 has already influenced the direction of climate change and adaptation policy implementation, and (3) respondents perceived (explicitly concerning the COVID-19 lockdowns of March-April 2020), that the pandemic has drawn attention away from climate policy. COVID- 19 has influenced the agenda of climate change research for more than half of the respondents and is likely to continue in the future, suggesting that the impacts on their research will still be felt for many years. The paper concludes by outlining critical implications for policy-making.